2005
DOI: 10.1002/ejic.200400947
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tertiary Phosphanes on the Coordination Configurations and Electrochemical Properties of Iron Hydrogenase Model Complexes: Crystal Structures of [(μ‐S2C3H6)Fe2(CO)6–nLn] (L = PMe2Ph, n = 1, 2; PPh3, P(OEt)3, n = 1)

Abstract: (6), PPh 3 (7), P(OEt) 3 (8)] were prepared as Fe-only hydrogenase-active-site models by controllable CO displacement of [(μ-pdt)Fe 2 (CO) 6 ] by tertiary phosphanes. The coordination configurations of 3-6 were characterized by X-ray crystallography. Disubstituted diiron complex 6 features an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
186
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(212 citation statements)
references
References 34 publications
25
186
1
Order By: Relevance
“…This provides the opportunity to synthesize the homologous S, Se, and Te series) (compounds 23-25). The increasing donor ability of Se and Te atoms in these complexes is reflected by the decreasing carbonyl stretching frequencies (the average ν CO [99] Contrary to the above-mentioned results, the catalytic activity of the complexes towards proton reduction from weak acids is substantially diminished from 23 to 24 and even more to 25. This trend was also reflected in DFT calculations, whereupon a disfavored ability to adopt the rotated structures and to provide a vacant coordination site was observed for anionic species.…”
Section: Structural Modelscontrasting
confidence: 77%
See 1 more Smart Citation
“…This provides the opportunity to synthesize the homologous S, Se, and Te series) (compounds 23-25). The increasing donor ability of Se and Te atoms in these complexes is reflected by the decreasing carbonyl stretching frequencies (the average ν CO [99] Contrary to the above-mentioned results, the catalytic activity of the complexes towards proton reduction from weak acids is substantially diminished from 23 to 24 and even more to 25. This trend was also reflected in DFT calculations, whereupon a disfavored ability to adopt the rotated structures and to provide a vacant coordination site was observed for anionic species.…”
Section: Structural Modelscontrasting
confidence: 77%
“…This trend is not unexpected, and similar shifts were already observed for sulfur-containing compounds. [99] In order to compare S, Se, and Te analogues and to investigate the influence of the heavier atoms, it is important to provide the same substitution pattern in the E-to-E linker (E = S, Se, Te). In a recent study, Weigand and co-workers extended the current investigations on [FeFe] hydrogenase model complexes containing the higher homologues by using the concept of a fixed backbone and prepared complexes 23, 24, and 25 with dithiolato, diselenolato, and ditellurolato ligands, respectively (Scheme 9).…”
Section: Structural Modelsmentioning
confidence: 99%
“…Nevertheless, trimethylphosphane reveals a similar donor character and can serve as an abiological surrogate for CN -. [15] Inspired by the properties of [2Fe2S(Si)] complexes and the natural abundance of the strong donor ligand CN -, [16] [FeFe] hydrogenase model complexes 1a-c (Scheme 2) were treated with triphenylphosphane and tetraethylammonium cyanide to afford monosubstituted, asymmetric [2Fe2S(Si)] cluster compounds. The resulting products were investigated according to their chemical and structural properties by cyclic voltammetry and crystal structure analysis.…”
Section: Scheme 1 Isocyanic Acid Complexesmentioning
confidence: 99%
“…Particular emphasis has been placed on variations of L, especially tertiary phosphines [1][2][3], but also isocyanides [4,5], N-heterocyclic carbenes [6][7][8][9], and cyanide [10][11][12][13]. While much effort has focused on functionalizing the dithiolate ligand [14][15][16][17][18][19][20], relatively little work has examined the possibility of replacing the thiolates with other bridging groups [21].…”
Section: Fe Complexes; Metal Hydride; Hydrogenase; Electrocatalysismentioning
confidence: 99%
“…Indeed, we found that HCl effected protonation at the Fe-Fe bond of 2, thereby forming a rare example of a (μ-hydrido)diiron azo system, [2H] + . 3 The complex was isolated as its salt from H 2 O/MeOH solution [32]. Interestingly, protonation of 2 afforded two solution isomers (Scheme 2), as indicated by doublet-of-doublet (unsymmetrical isomer) and triplet (symmetrical isomer) 1 (CO) 4 (PMe 3 ) 2 and Fe 2 (S 2 C 3 H 6 )(CO) 4 (PMe 3 ) 2 gives only a trans-dibasal isomer, even at low temperatures [32].…”
mentioning
confidence: 99%